PENERAPAN METODE GREEN QUALITY FUNCTION DEPLOYMENT II UNTUK PENGEMBANGAN PRODUK PADA UKM KAHLA TEMPE CRISPY SUKABUMI - Dhiyaginaa Nurayuni; Roni Kastaman; Faizal Syahmurman (Universitas Galuh, 2023)
Tempe chips are simple preparations that have a new taste from consuming tempe. The tight competition between tempe chips business requires SMEs Kahla Tempe Crispy to continue to innovate and improve quality periodically. Tempe chips must be quality and guaranteed food safety for the community and the environment. This study aims to determine the attributes of products needed and desired by consumers Kahla Tempe Crispy with attention to the environment and costs in the production process through the method of Green quality function Deployment II. This method not only considers the quality aspect but also considers the environmental and cost aspects into the matrix, which is described in the Matrix House of Quality, Green House, Cost House, and Comparison House. House of Quality research results show there are 5 attributes that have been met by Kahla Tempe Crispy. Based on the Green House, there are 2 processes that have Critical Control Point and there are solid, liquid and gas waste from production. Through the value engineering method by replacing with a flat frying pan can reduce the cost of cooking oil for 1 year by Rp. 4.608.000. And the profit obtained by using a flatfrying pan of Rp. 1,238,630,400 or greater Rp. 606,412,800 from a concave pan.On the matrix Concept Comparison House produces the best wok product concept for the production process of tempe chips are effective and efficient and meet the criteria Q.E.C (Quality, Environment, Cost). With the performance value of flat frying pan is higher (275) than concave frying pan (253), and the cost of flat frying pan is more economical (Rp. 347,753,592) from a concave pan (Rp. 351.968.592).